Sharia-compliant VS Conventional Mutual Fund in Indonesia: An Evaluation Based on Portofolio Performance - Alfalisyado Alfalisyado; Ali Akbar Anggara* (Universitas Syiah Kuala, 2023)
This study aims to compare performance between Sharia-compliant mutual funds and conventional mutual funds which classified as share mutual funds, fixed-income mutual funds and mixed mutual funds. It observes a 60-month period spanning from 2018 to 2022, evaluating mutual fund performance through key indicators, including return ratio, Sharpe Ratio, Treynor Ratio, Jensen Alpha, and Assets Under Management (AUM). The findings reveal notable differences in the performance of equity, fixed-income, and balanced mutual funds, with Sharia-compliant mutual funds consistently demonstrating superior average performance compared to their conventional counterparts. This study contributes valuable insights to the portfolio literature, offering investors and financial professionals critical information for informed investment decisions.